"Drug expert: Notre Espoir" / Dr. Mohd Nadzri Mohd Najib and Dr. Siti Syairah Mohd Mutalip - Mohd Najib, Mohd Nadzri; Mohd Mutalip, Siti Syairah (Faculty of Pharmacy, 2023)
In response to the call to actively engage in the community services and knowledge transfer events, an educational program named "Drug Expert; Notre Espoir'' was successfully organized on 6th January 2023. Officiated by En. Amer Herberd Abdullah (Deputy Rector of Bertam Campus), this program was participated by 39 primary school students accompanied by 3 teachers from the Kelab SETEM dan Doktor Muda, SK Kg. To' Bedor.The term "Notre Espoir'' means "Our Hope" in English, which embodies the aim to introduce young students to the field of pharmacy and the responsibilities of pharmacists in maintaining the health and wellbeing of individuals.